Novel insights into athlete physical recovery concerning lactate metabolism, lactate clearance and fatigue monitoring: A comprehensive review - Huang, Tianhao; Liang, Zeyu; Wang, Ke; Miao, Xiangjun; Zheng, Lei (Frontiers in Physiology, 2025)
Lactate accumulation will appear in athlete skeletal muscle after intense exercise. If the high lactate level maintains, athletes will sustain fatigue and athletic capacity decline due to internal environment and normal metabolism disruption. In order to enhance athlete physical recovery and exercise performance in high-intensity sport events, it is of great significance to explore the scientific intervention procedures based on quicker lactate clearance in skeletal muscle and blood after exercise. This article collects classic and novel literature in terms of lactate metabolism, lactate clearance and fatigue monitoring during exercise by searching PubMed database and then summarizes comprehensive insights into athlete physical recovery with corresponding figures and charts. We introduce the generation and transformation process of lactate, lactate clearance pathways and the fatigue monitoring methods for athletes in detail. The lactate clearance pathways involve biochemical pathways (oxygen inhalation, amino acids supplement, targeting free radical, alkaline reserve, targeting vasomotion, ribose supplement), physical activities (exercise-mediated activities, non-exercise activities) and training methods (interval training, altitude training) to accelerate lactate metabolism. The biochemical factors for monitoring athletic fatigue level involve blood, urine, sweat, saliva and exhaled gas. We hope this review can offer some significant and scientific assistance for athlete recovering after exercise and improving sport achievements based on quicker lactate clearance.